ON THE PENETRATION OF AN ELASTIC PLASTIC MATERIAL BY A SLENDER BODY - Norbury, J; Wheeler, A (1987)
We develop a conventional slender-body theory to consider the penetration of a slender body into an elastic-plastic material with a von Mises yield condition. We show that (i) stress and strain fields are well approximated by a cavity-expansion solution, and (ii) the Jaumann terms may be neglected when the shear modulus is large, the material behaving as an elastic-plastic composite with a boundary-layer transition. © 1987 Oxford University Press.